Investigating Tendencies of Malaysian Muslims in Islamic Estate Planning: Insight into Its Determinants - Abd Wahab, Norazlina; Maamor, Selamah; Hashim, Suraiya; Zainol, Zairy; Yaacob, Hakimah (Universiti Sains Islam Malaysia, 2021)
Estate planning is one of the crucial elements of managing property during a person’s lifetime. It involves both handling and managing property during one’s lifetime and after death. For Muslims, the objectives of Shariah, which are known as Maqasid Shariah, can be attained if their finances are planned in a wise and cost-effective manner. Unfortunately, it was reported that frozen inheritance assets have steadily increased from the day of Independence, amounting to RM70 billion in 2020 indicating the seriousness of the matter. The freezing of inheritance property is detrimental to the economy and thus opposes the spirit of Maqasid Shari’ah which recommends that it should be properly managed for the benefit of the public. This is where estate planning plays its role in ensuring quicker and easier distribution of assets and property. Hence, the objective of this research is to investigate Malaysian Muslims’ tendencies in estate management planning and its determinants. A total of 406 respondents throughout Peninsular Malaysia responded to the prepared survey, where the Partial Least Squares Structural Equation Modelling (PLS-SEM) approach was employed as the main data analysis for this study. The findings revealed that altruism, advantages and compliance were significant in influencing tendencies of Malaysian Muslims in Islamic estate planning. Surprisingly, service was found to be an insignificant factor in influencing the tendencies of Malaysian Muslims in Islamic estate planning. This study provides some insights on the role of policymakers and estate planning related industry in ensuring the compliance of estate planning product and increasing the awareness of Muslims to do estate planning by promoting the advantages and importance of doing so. Policymakers are also welcome to engage in this matter by providing earlier education on Islamic estate planning among Muslims in Malaysia